Determination of the effect of Nigella sativa on blood pressure; a systematic review and meta-analysis of randomized clinical trials - Moloud Fakhri; Mohammad Yousofpour; Mahmood Moosazadeh; Alireza Fatahian; Mohammad Azadbakht; Melina Ramezanpour (Society of Diabetic Nephropathy Prevention, 2024)
Introduction: Hypertension is considered a significant and highly prevalent public health problem. Due to the wide application of the medicinal herb Nigella sativa in managing this condition, the present study aims to evaluate the effect of N. sativa consumption on reducing blood pressure (BP) levels using a systematic review and meta-analysis approach. Materials and Methods: Multiple online databases, including PubMed, Scopus, Cochrane, Web of Science, and the Google Scholar search engine, were searched using standard keywords to identify relevant articles up to May 9, 2022. Data were analyzed using STATA 14 software, and the significance level was taken as P<0.05 for all tests. Results: From the total of 12 reviewed studies with a sample size of 854, the consumption of N. sativa powder (SMD: -0.46; 95% CI: -0.63, -0.30) and N. sativa oil (SMD: -2.04; 95% CI: -2.75, -1.34) lowered the systolic BP (SBP) levels. The consumption of N. sativa powder (SMD: -0.45; 95% CI: -0.63, -0.28) and N. sativa oil (SMD: -2.31; 95% CI: -3.05, -1.57) altered the diastolic BP (DBP) level. Then, the standard effect sizes of N. sativa consumption on triglyceride (SMD: -0.14; 95% CI: -0.29, 0), LDL-C (SMD: -0.35; 95% CI: -0.54, -0.17), HDL-C (SMD: 0.01; 95% CI: -0.14, 0.16) and FBS (SMD: -0.36; 95% CI: -0.58, -0.15) levels were measured. Conclusion: Nigella sativa consumption showed a higher impact on reducing SBP than DBP levels. In addition, the consumption of N. sativa oil was more effective in lowering BP levels than N. sativa powder. Hence, further research is suggested to evaluate and compare the effectiveness of N. sativa oil and powder. Registration: This study has been compiled based on the PRISMA checklist, and its protocol was registered on the PROSPERO website (ID: CRD42022336951).